1983
DOI: 10.1037/0022-3514.45.1.210
|View full text |Cite
|
Sign up to set email alerts
|

On the social advantages of having an older, opposite-sex sibling: Birth order influences in mixed-sex dyads.

Abstract: This study examined the influences of birth order on behavior occurring in the initial, unstructured interactions of 40 mixed-sex dyads composed of a man and a woman who each had a sibling of the opposite sex. The design contrasted four different dyad types: (a) a firstborn man paired with a firstborn woman, (b) a firstborn man paired with a last born woman, (c) a last born man paired with a firstborn woman and (d) a last born man paired with a last born woman. Results indicated that individuals with an older,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…First, in accordance with social learning theory (Mischel, 1966), a series of studies has shown that laterborns model their behavior after their older siblings, assuming sex-typed qualities similar to those of their sisters or brothers (Bigner, 1972;Brim, 1958;Greenfield & Weatherley, 1986;Koch, 1960;Rosenberg & Sutton-Smith, 1964, 1968Sutton-Smith & Rosenberg, 1965, 1970. Along these lines, two studies that examined the relationship between sibling sex constellation and older adolescents' interaction styles found some support for a modeling hypothesis (Greenfield & Weatherley, 1986;Ickes & Turner, 1983). Based on a study of college-aged students with older versus younger opposite-sex siblings, Ickes and Turner (1983) reported that males who had older sisters displayed more expressive qualities (e.g., initiated more conversation, asked more questions) in dyadic interactions with an unknown member of the opposite sex.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…First, in accordance with social learning theory (Mischel, 1966), a series of studies has shown that laterborns model their behavior after their older siblings, assuming sex-typed qualities similar to those of their sisters or brothers (Bigner, 1972;Brim, 1958;Greenfield & Weatherley, 1986;Koch, 1960;Rosenberg & Sutton-Smith, 1964, 1968Sutton-Smith & Rosenberg, 1965, 1970. Along these lines, two studies that examined the relationship between sibling sex constellation and older adolescents' interaction styles found some support for a modeling hypothesis (Greenfield & Weatherley, 1986;Ickes & Turner, 1983). Based on a study of college-aged students with older versus younger opposite-sex siblings, Ickes and Turner (1983) reported that males who had older sisters displayed more expressive qualities (e.g., initiated more conversation, asked more questions) in dyadic interactions with an unknown member of the opposite sex.…”
Section: Introductionmentioning
confidence: 92%
“…Along these lines, two studies that examined the relationship between sibling sex constellation and older adolescents' interaction styles found some support for a modeling hypothesis (Greenfield & Weatherley, 1986;Ickes & Turner, 1983). Based on a study of college-aged students with older versus younger opposite-sex siblings, Ickes and Turner (1983) reported that males who had older sisters displayed more expressive qualities (e.g., initiated more conversation, asked more questions) in dyadic interactions with an unknown member of the opposite sex. Other work, also focused on college-aged youth, suggested that having a sister was associated with greater perceived comfort in interactions with a same-sex friend (Greenfield & Weatherley, 1986).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations